Silver lady - Putney, Mary Jo (Putney, Mary Jo. Dangerous gifts, 2023)
"A sense of duty sends Bran Tremayne to Cornwall to confront his heritage of British nobility. Abandoned at birth, Bran wants nothing to do with the embittered remains of his family. But as a special agent for the Home Office, he senses trouble brewing along the coast. And he can't turn away from the vulnerable woman he encounters in the Cornish countryside. Merryn's amnesia makes her past a mystery to them both, but with her life in danger, the only thing Bran knows for sure is that the beautiful stranger needs his protection ... Leaning into Bran is difficult enough, but can Merryn trust the strong bond--and the powerful passion--she feels for her rugged rescuer? She has no choice once Bran uncovers that she is at the center of a plot between French agents and Cornish smugglers. From misty woodlands to stormy shores, the two join forces with a band of loyal Cornishmen to bring down a common enemy. Yet will their growing love survive the coming peril?"--